Diversity and Inclusion Marketing for Brand Building - Petrauskaitė, Ieva (Jaunųjų mokslininkų darbai, 2025)
Due to evolving market trends, changing consumer needs, globalisation, social responsibility, and the demand for sustainable development, diversity and inclusion marketing has become increasingly important for brands. Despite its growing relevance in academic literature, no clear, step-by-step guidelines exist to help brands implement it effectively. This study aims to fill that gap by theoretically demonstrating the benefits of diversity and inclusion marketing and creating practical guidelines for its application. The study explores how such marketing strategies can strengthen a brand. In the first section, we define diversity and inclusion marketing and the conditions under which it can be effectively applied. The second section highlights its importance for brand development, while the third presents a roadmap for implementation. These guidelines can assist companies, managers, and marketers in initiating and applying diversity and inclusion marketing. They emphasise how it can help retain customers, understand their needs, and build meaningful connections. Additionally, it supports the creation of relevant content and fosters positive engagement among employees and management, encouraging innovation. Overall, the study offers a structured approach to using diversity and inclusion marketing as a strategic tool for brand growth and resilience.
Keywords: diversity and inclusion marketing; diversity; inclusion; brand building